Heterosis and combining ability in bell pepper lines with resistance to multiple pathogens (Revista Ciência Agronômica, 2023)
The aim of this study was to develop bell pepper hybrids with resistance to multiple pathogens and makeinferences in regard to components of heterosis in hybrids obtained from lines presumed to be resistant to Pepper yellowmosaic virus (PepYMV), Phytophthora capsici, or Meloidogyne incognita. The studies were carried out in a greenhouse. Weused ten lines, thirty experimental hybrids, and seven controls (Konan-R, Magali-R, Martha-R, Stephany, Mallorca, MagnataSuper, and Criollo de Morelos-334). For all experiments, a randomized block design was used with three replications (withplots composed of 16 plants). For evaluation of the reactions to P. capsici and to PepYMV, the percentages of asymptomaticplants were considered. For evaluation of the reactions to M. incognita, the reproduction index and the reproduction factorof the nematode were calculated. The additive gene effects were important for all the traits evaluated, and for percentage ofplants resistant to PepYMV and P. capsici, the non-additive effects were also important. The alleles that control resistance toPepYMV, to P. capsici, and to M. incognita have a degree of dominance near 1, in absolute value, which indicates a favorablesituation for obtaining hybrids that accumulate multiple resistance to these pathogens.